OPTIMALISASI KONTEN VISUAL PADA PLATFORM DIGITAL RUMAH PENDIDIKAN SEBAGAI MEDIA INFORMASI LAYANAN KEMENDIKDASMEN - Taranian Olifia, Happy; Sutisna Riyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation requires government institutions to present public service information attractively. However, the Digital Service Utilization division of Pusdatin Kemendikdasmen faces challenges due to bureaucratic documents on the Rumah Pendidikan platform that are rigid and dense, risking audience fatigue. This study aims to analyze the production management workflow, Visual Communication Design (VCD) elements, and public information transformation strategies to overcome bureaucratic rigidity. The method employed is descriptive qualitative, with data collected through in-depth interviews, participative observation, and visual asset documentation. The study reveals that content pre-production is systematically managed through weekly meetings planned one month prior to publishing. The implementation of VCD elements consistently safeguards brand identity using sans-serif typography (Inter and Nunito), mandatory color codes (blue for Ruang Guru GTK, orange/yellow for Ruang Murid), and layout safe zones. Furthermore, the strategy successfully transforms dense texts into dynamic Instagram feeds carousel and storytelling-based reels, alongside adaptive presentation-deck layouts on the Bimtek Guru Pejuang Digital (GPD) guidelines. Visual content optimization effectively delivers ministry public services in a concise, aesthetic, and professional manner.